Radiation Dose Escalation in Stage III Non-Small-Cell Lung Cancer - Sause, William T.; Terakedis, Breanne (Frontiers in Oncology, 2011)
For patients with stage III non-small-cell lung cancer with unresectable or inoperable tumors, definitive chemoradiotherapy is often utilized. Historically, local control and overall survival rates have been poor. In an effort to improve local control, new chemotherapeutic agents in combination with higher doses of radiotherapy have been investigated. Early dose escalation trials date back to the 1980s, and the feasibility and efficacy of dose escalation for patients with inoperable stage III lung cancer continue to be topics of investigation. Herein, we review the evolution of chemotherapy as it relates to treatment of unresectable stage III lung cancer, and we outline the early and the more recent dose escalation studies. While dose escalation appears to provide a modest benefit in terms of preventing local failure and improving overall survival, advances in diagnostic imaging and radiotherapy treatment have possibly resulted in selection of a more favorable patient population. These variables make statements regarding the benefit of dose escalation challenging.